EMBRIOGENESIS IKAN CUPANG (Betta splendens) - Annur, Annur; Madinawati, Madinawati; Mangitung, Septina Fifi; Rusaini, Rusaini (FAPETKAN UNTAD, 2016)
Siamese fighting fish (Betta splendens) is a freshwater ornamental fish that has a potential both in the domestic market and international market (export). Some studies on biological aspects of the Siamese fighting fish have been conducted.Â However, information on the embryonic development of the fighting fish is lack.Â The study aims to determine the stage of embryonic development in fighting fish. The experiment was conducted at the Laboratory of Aquaculture, Faculty of Animal Husbandry and Fisheries, Tadulako University, Palu. The results showed that the development of fish embryo can be divided into several stages, including cleavage, morula, blastula, gastrula, and organogenesis. The egg of the fighting fish was hatch in 35 hours after fertilization.Â Key words: Betta splendens, fish egg, embryogenesis, and larvae